Interfacial self-assembly of gold nanoparticle-polymer nanoconjugates into microcapsules with near-infrared light modulated biphasic catalysis efficiency. Issue 72 (21st August 2019) - Su, Jiaojiao; Wang, Shengliang; Xu, Zhijun; Wu, Guangyu; Wang, Lei; Huang, Xin
Abstract : Gold nanoparticle-based microcapsules based on the interfacial assembly significantly enhanced the biphasic catalytic reaction rate upon near-infrared light irradiation. Abstract : A high throughput way to generate gold nanoparticle-based microcapsules was demonstrated based on the interfacial assembly in a water and 2-ethyl-1-hexanol two phase system. The obtained gold microcapsules exhibit superior stability, good flexibility, ductility, and a significant enhancement (about 10-fold) in the biphasic catalytic reaction rate upon near-infrared light irradiation.